2007
DOI: 10.1002/gps.1855
|View full text |Cite
|
Sign up to set email alerts
|

Mild cognitive impairment: coping with an uncertain label

Abstract: MCI patients encounter stress-inducing practical, social and psychological difficulties. Based on the current preliminary findings, the key themes for an MCI support-group programme should include the provision of information about the syndrome's causes, course, concomitant symptoms, attributions, social consequences, and available treatments. The impact of receiving an MCI label warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
123
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(128 citation statements)
references
References 22 publications
3
123
0
Order By: Relevance
“…Furthermore, the programme addressed topics known to pose serious problems in MCI patients [5] . However, individual differences during the intervention were considerable, which may explain why two of the three secondary outcome measures failed to show a change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the programme addressed topics known to pose serious problems in MCI patients [5] . However, individual differences during the intervention were considerable, which may explain why two of the three secondary outcome measures failed to show a change.…”
Section: Discussionmentioning
confidence: 99%
“…These rates also imply that for a large proportion of MCI patients the progression of their illness is uncertain, and that the diagnosis may, rather than diminish their feelings of uncertainty, even exacerbate them. Although MCI patients can by definition still function independently in everyday life, they do encounter a multitude of difficulties because of the mild cognitive changes, inducing profound stress, which, in turn, causes more practical, social and psychological problems [5,6] . In line with these findings, Hwang et al [7] showed that the incidence of mood disorders, such as dysphoria, anxiety, restlessness or irritability, was higher in MCI patients than in healthy age-matched controls.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, older adults with MCI were able to accurately identify their cognitive symptoms, described some negative consequences of MCI, had diverse emotional responses to their diagnosis, and felt uncertain about whether there would be any progression to AD. Only two studies have examined behaviors after a diagnosis of MCI [7,8]. In these studies, older adults engaged in self-care behaviors, such as use of supportive services and engaged in strategies to prevent dementia.…”
Section: Introductionmentioning
confidence: 98%
“…Relatively few descriptive and qualitative studies have examined what people think or believe about MCI [6][7][8][9][10][11]. In these studies, older adults with MCI were able to accurately identify their cognitive symptoms, described some negative consequences of MCI, had diverse emotional responses to their diagnosis, and felt uncertain about whether there would be any progression to AD.…”
Section: Introductionmentioning
confidence: 99%
“…5,7 At the individual level, while still functioning in their day-to-day activities, persons with MCI are confronted with a variety of cognitive problems that cause them anxiety and distress. [8][9][10][11] For example, several qualitative studies have shown that persons with MCI are confronted with feelings of social isolation, uncertainty and apprehension, which might be a result of the ambiguity of the diagnosis, of fear of embarrassment or from reduced self confidence. 9,12 Finally, given these difficult psychological experiences, it is not surprising that the consequences of MCI at the family level are also detrimental.…”
Section: Introductionmentioning
confidence: 99%